Does climate change affect enterprises’ ability to sell their products? - Yu, Siming; Cai, Cheng; Zhang, Shuocheng; You, Peng (Frontiers in Ecology and Evolution, 2022)
Based on the climate change data of local cities and the operating income data of listed Chinese enterprises from 2008 to 2019, this paper studies the impact of enterprise change on enterprises' sales capacity, and analyzes the path of climate change on enterprises' sales revenue from three different perspectives: inside enterprises, supply side and demand side. The results show that climate change reduces the sales revenue of enterprises, and the mechanism shows that: from the internal perspective of enterprises, climate change reduces the production efficiency and increases the management cost, and the impact on the sales cost is not obvious. From the demand side, climate change increases business risks and reduces transactions between large customers and enterprises. The sales share from large customers reduces, which has no obvious impact on small customers. On the supply side, climate change reduces business credit levels, which in turn reduces sales revenues. Heterogeneity analysis shows that the impact of climate change on sales revenue is more obvious in private enterprises, weak internal control and enterprises in central and western regions.